2017
DOI: 10.1097/aog.0000000000002319
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Vein Thrombosis

Abstract: Ovarian vein thrombosis is a rare thrombotic condition with an incidence 60-fold lower compared with leg DVT in our institution. The striking association with cancer adversely affects overall survival rates in patients with ovarian vein thrombosis. Venous thromboembolism recurrence rates argue for anticoagulation with a direct oral anticoagulant or vitamin K antagonist, particularly in those with a history of venous thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 22 publications
0
31
0
2
Order By: Relevance
“…Plastini et al found that in patients with OVT treated with anticoagulation and in those without treatment there was no correlation found in terms of overall outcome [11]. However, a recent case-control study by Lenz CJ et al looked at the risk of venous thromboembolism recurrence, major bleeding and mortality among those who got diagnosed with ovarian vein thrombosis and found that although patients with OVT are treated less often (54%) as compared to patients who got diagnosed with lower extremity DVT (98%), the recurrence rate of venous thromboembolism was similar between these two groups (2.3% in OVT vs 1.8 in DVT ) arguing that anticoagulation with a direct oral anticoagulation or vitamin K antagonist should be considered especially in patients who have a personal history of venous thromboembolism [1]. We choose to administer the patient with anticoagulant and she did respond well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plastini et al found that in patients with OVT treated with anticoagulation and in those without treatment there was no correlation found in terms of overall outcome [11]. However, a recent case-control study by Lenz CJ et al looked at the risk of venous thromboembolism recurrence, major bleeding and mortality among those who got diagnosed with ovarian vein thrombosis and found that although patients with OVT are treated less often (54%) as compared to patients who got diagnosed with lower extremity DVT (98%), the recurrence rate of venous thromboembolism was similar between these two groups (2.3% in OVT vs 1.8 in DVT ) arguing that anticoagulation with a direct oral anticoagulation or vitamin K antagonist should be considered especially in patients who have a personal history of venous thromboembolism [1]. We choose to administer the patient with anticoagulant and she did respond well.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian Vein Thrombosis (OVT) is a relatively rare and uncommon thrombotic condition commonly attributed to the postpartum period. It has been shown to complicate 1 in 600 to 1 in 1200 pregnancies [1]. It is more common after cesarean section than spontaneous vaginal delivery [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current clinical practice is that patients with acute GVT are treated with anticoagulation for 3 to 6 months. 6,7,28,29 Information about the use of DOACs for GVT is limited to a few case reports. 27,30 It continues to be the practice of Mayo Thrombophilia Clinic to provide anticoagulant therapy that includes also DO-ACs to patients with GVT in the absence of a direct contraindication, such as major bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…27,30 It continues to be the practice of Mayo Thrombophilia Clinic to provide anticoagulant therapy that includes also DO-ACs to patients with GVT in the absence of a direct contraindication, such as major bleeding. 6,27 Renal vein thrombosis Renal vein thrombosis (RVT) is highly associated with underlying malignancy, particularly renal cell carcinoma. 5 Invasion of this cancer to the renal vein with extension to the inferior vena cava is often called tumor thrombus and thought not to require anticoagulation.…”
Section: Introductionmentioning
confidence: 99%